2018
DOI: 10.1186/s13287-018-1025-8
|View full text |Cite
|
Sign up to set email alerts
|

Physiological cyclic hydrostatic pressure induces osteogenic lineage commitment of human bone marrow stem cells: a systematic study

Abstract: BackgroundPhysical loading is necessary to maintain bone tissue integrity. Loading-induced fluid shear is recognised as one of the most potent bone micromechanical cues and has been shown to direct stem cell osteogenesis. However, the effect of pressure transients, which drive fluid flow, on human bone marrow stem cell (hBMSC) osteogenesis is undetermined. Therefore, the objective of the study is to employ a systematic analysis of cyclic hydrostatic pressure (CHP) parameters predicted to occur in vivo on early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 50 publications
1
46
0
Order By: Relevance
“…We contribute this response to a possible physiologic mechanism, as pressure transients fluctuate within the bone in response to mechanical loading (7,47). However, we recognize that differences in the bioreactor setup and stimulation protocols may also contribute to divergent observations (15). Nonetheless, our observations that physiologic low-magnitude cyclic pressure transients, which represent the precursor to fluid shear in vivo, are sufficient to directly drive MSC osteogenesis independent of fluid flow.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…We contribute this response to a possible physiologic mechanism, as pressure transients fluctuate within the bone in response to mechanical loading (7,47). However, we recognize that differences in the bioreactor setup and stimulation protocols may also contribute to divergent observations (15). Nonetheless, our observations that physiologic low-magnitude cyclic pressure transients, which represent the precursor to fluid shear in vivo, are sufficient to directly drive MSC osteogenesis independent of fluid flow.…”
Section: Discussionmentioning
confidence: 88%
“…A number of recent studies have demonstrated that pressures up to 300 kPa can drive MSC osteogenesis as depicted by up-regulation of the osteogenic-associated genes cyclooxygenase 2 (Cox2), runt related transcription factor 2 (Runx2), distal-less homeobox 5, osterix, osteopontin (Opn), and alkaline phosphatase (8,9). Moreover, low bone physiologic pressures (kilopascal range) were sufficient to promote mineralization of human (h)MSCs, further supporting the importance of pressure in regulating osteogenic lineage commitment (8)(9)(10)(11)(12)(13)(14)(15). Despite this clear osteogenic response to pressure stimulation, little is known about how MSCs sense and transduce pressure mechanical cues, with only one study to date highlighting the involvement of mechanosensitive ion channel Piezo 1 (9).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…These concentrations represent minimal levels for the support of osteogenesis. 32,37 The role Figure 3C, and listed in Table 1. Within these proteins, significant enrichment (enrichment factor > 1.7, P < 10 -4 ) of several "extracellular" GOCC terms was shown in comparison to the total 393 identified proteins using Fisher's exact test, with enrichment of UniProt keywords "secreted" and "signal" (enrichment factor > 1.6, P < 10 -5 ) also occurred ( Figure 3D).…”
Section: Assessing Osteogenic Differentiation Of Mscs Via Alp Activitymentioning
confidence: 99%
“…Dissecting the individual contributions of bone‐resident versus marrow‐resident cells on bone adaptation is challenging. Individual bone marrow–resident cells have been studied in in vitro culture and subjected to mechanical loads, demonstrating that the relevant cells are mechanosensitive. Coculture has further demonstrated that both mesenchymal and hematopoietic lineage cells in the marrow interact with osteocytes and osteoblast precursors through various signaling pathways .…”
Section: Bone Mechanobiologymentioning
confidence: 99%